Մարդասպան կնոջ տիպաբանությունը և նրանց կողմից կատարված սպանությունների հոգեբանական մեխանիզմների պարզաբանման հիմնախնդիրը - Գայանե Իսկանդարյան (ՀՀ ԳԱԱ հրատ.)
В статье представлены типы женщин-убийц, а также мотивы совершенных ими убийств. Мотивы совершенных женщинами убийств являются результатом психологического состояния личности. This paper presents the typology of homicidal women and identifies the motivations behind the homicides. These motivations are the result of the interaction of the psychological state (and of situational nature, such as defense), personal.
Keywords: Philosophy; Psychology; Religion